Nodal disease burden and outcome of medullary thyroid carcinoma. Issue 2 (27th October 2020) - Moses, Lindsey E.; Oliver, Jamie R.; Rotsides, Janine M.; Shao, Qianhui; Patel, Kepal N.; Morris, Luc G. T.; Givi, Babak
Abstract: Background: Medullary thyroid carcinoma (MTC) is a rare malignancy with high incidence of cervical lymph node (CLN) metastasis. We investigated the impact of nodal disease burden on survival. Methods: We searched the National Cancer Database for MTC patients treated surgically. Impact of nodal metastasis on survival was analyzed using Cox univariable and multivariable regression. Results: We identified 2627 patients from 2004 to 2015. Positive CLNs were identified in 1433 (54.5%), and 542 (20.6%) had >10 CLN+. Overall survival was 94.5% and 89.6% at 3 and 5 years. Patients with 11 to 20 CLN+ had significantly worse survival than patients with 1 to 10 CLN+ in univariable and multivariable analyses (HR = 3.56 (2.31‐5.50) vs 2.26 (1.60‐3.20); P  < .0001). The ratio of positive to dissected CLN was associated with overall survival. Conclusions: Higher burden of nodal disease is associated with worse survival in MTC. The number of positive nodes could be a valuable prognosticator in addition to the current staging system.